Makna Denotatif dan Makna Konotatif dalam Kajian Semantik pada Lirik Lagu “Mangu” oleh Fourtwnty - Indah Sari; Khairiyah Putri; Fatmawati Fatmawati (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to analyze the denotative and connotative meanings found in the lyrics of the song “Mangu” by Fourtwnty using a qualitative semantic approach. The song was selected due to its rich lyrical structure, filled with symbolism, emotional depth, and spiritual reflection, making it a compelling subject for linguistic analysis. The data was obtained through the documentation of the song’s lyrics and then analyzed by identifying, classifying, and interpreting words or phrases that potentially carry dual meanings. The findings indicate that the lyrics of “Mangu” contain denotative meanings that refer to the literal definitions of words, as well as connotative meanings that imply emotional, symbolic, and spiritual messages. Several phrases, such as “arah kiblat” (direction of prayer), “cara berdoa” (way of praying), and “kumadah” (I offer), carry deep connotations reflecting differences in life perspectives and spiritual values within a relationship. The analysis reveals that the conflict in the song is not merely romantic but also existential, highlighting a separation driven by differing beliefs and life interpretations. This study emphasizes the importance of understanding connotative meaning in interpreting song lyrics as a form of complex language expression and contributes to the enrichment of semantic studies in popular literary works.